Dampak Rendahnya Dukungan Orang Tua Terhadap Prestasi Akademik Dan Kondisi Emosional Siswa - Moses Adeleke Adeoye; Ridho Kurniawan; Rahaji Sinaga (Jurnal Zeniusi, 2026)
This study aims to analyze the impact of low parental support on student achievement and emotional well-being at the secondary education level. Using a qualitative approach and descriptive survey methods, data were collected through open-ended questionnaires distributed online to students in several urban areas in Indonesia, and triangulated through interviews and consultations with guidance and counseling teachers. The results indicate that low parental involvement, both academically and emotionally, has a direct impact on decreased learning motivation, limited understanding of material, and impaired psychological well-being. Students who do not receive attention or validation from their parents tend to experience feelings of neglect, stress, and ongoing anxiety. Furthermore, negative parental responses to academic failure exacerbate the emotional distress experienced by students. These findings emphasize the importance of active and empathetic parental involvement in supporting children's learning. This study recommends the need for strategic collaboration between schools and families through parenting training, teacher-parent communication forums, and family-based intervention programs to create a supportive and sustainable educational ecosystem.